An Analysis of Textbook Entitled “Pathway to English” Published By Erlangga at the First Semester of the 11th Grade of Senior High School - Rohmatillah, Rohmatillah; Pratama, Devi Audina (Universitas Islam Negeri Raden Intan Lampung, 2017)
The purpose of this study was to find out whether the Pathway to English textbook of the eleventh grade at the first semester fulfilled syllabus points of the 2013 curriculum and how broad they presented. The researcher used descriptive qualitative research. The data would be gathered from document analysis of an English textbook entitled Pathway to English published by Erlangga. The Pathway to English textbook had fulfilled syllabus points of 14 from 16 items of basic competence and 6 from 6 items of learning material. Each basic competence was provided in some exercises of 4 English skills. The learning materials were successfully included and developed supported materials which interpreted about social function formed cooperating tasks, text structures were available and related the other rules of text structures, and language features were available and were developed based on suitable vocabulary, exercise of pronunciation and intonation, and related grammar to support the materials of modals, adverb, tenses, connector, etc. It was also provided and developed appropriate topics and multimedia using based on the syllabus guidance. On the other hand, this textbook had weakness about there were not available BC 4.5 and BC 4.6 criteria and lack notes of enrichment vocabulary and pronunciation.